The Impact of Business Environment and Organizational Culture on The Implementation of Management Accounting Information System in Some Hotels - Widia Astuty; Fajar Pasaribu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to prove empirically: (1) The influence of the business environment on the implementation of Management Accounting Information System; (2) The influence of organizational culture on the implementation of Management Accounting Information System; and (3) the influence of the implementation of Management Accounting Information System to the quality of Management Accounting Information. The research method used is explanatory research. The target population is the sample in this research which is conducted by taking all the hotels service company in North Sumatra as the unit of analysis (census), whereas the respondents in this research are the hotel managers by using questionnaire instrument as a tool to collect the data. The results of this study indicate that the business environment has no effect on the implementation of Management Accounting Information System. Meanwhile the organizational culture affects the application of management accounting information systems as well as affect the quality of Management Accounting Information.